Essays on Japan from Japan (Maruzen, Showa 62, 1987)
Many aspects of Japanese culture, as can be seen in the twelve articles, differ from those of other cultures in other climates. These articles will also give the reader a sense of how deeply Japanese culture is rooted in the culture of humanity as a whole.